Banking Ïinduciaíy Píinciples in Anticipating Bad Loan Default (PT Bank BTPN Mitra Usaha Rakyat Tbk Teluk Betung Bandar Lampung Branch) - Marwan, Marwan; Anggraini, Rika; Iza, Noor (Journal of Law, Politic and Humanities, 2024)
Credit provided by banks basically contains risks, so in its implementation banks must pay attention to sound credit principles, including banks are not allowed to provide credit without a written agreement. Efforts to reduce the risk of loss in providing credit, require credit guarantees in the sense of confidence in the ability and ability of debtors to pay off their debts in accordance with the agreement. The problems in this study are: (1) How is the existence of the implementation of individual guarantees for lending to PT Bank BTPN Mitra Usaha Rakyat Tbk Teluk Betung Bandar Lampung Branch in the perspective of the Banking Law and legal guarantees? (2) What are the legal implications for default in the implementation of individual guarantees for lending to PT Bank BTPN Mitra Usaha Rakyat Tbk Teluk Betung Bandar Lampung Branch? The research approach used is a socio-legal research approach. Research data is sourced from doctrinal and non-doctrinal research data. The data is then processed through data selection, data classification and data preparation, then analyzed qualitatively. The results show: (1) The existence of individual guarantees for lending to PT Bank BTPN Mitra Usaha Rakyat Tbk Teluk Betung Bandar Lampung Branch in the perspective of the Banking Law is in accordance with the provisions of Article 8 that in providing credit, Commercial Banks must have confidence in the ability and ability of debtors to pay off their debts in accordance with the agreement. Meanwhile, from the perspective of legal guarantees, additional collateral is in accordance with Bank Indonesia policy. The receipt of collateral in the form of individual guarantees is basically only as an addition to confidence that the credit will run well due to the control of the insurer over the health of the debtor's business. (2) The legal implication for the occurrence of default in the implementation of individual guarantees for lending to PT Bank BTPN Mitra Usaha Rakyat Tbk Teluk Betung Bandar Lampung Branch is that the bank can directly collect the Guarantor to fulfill its obligations, if in the agreement the guarantor has expressly waived the privilege to demand that the debtor's assets be confiscated first. The Bank can collect the Guarantor through a lawsuit in the District Court and then execute it.